Serial rotational thromboelastography (ROTEM) in mechanically ventilated patients with COVID-19 demonstrates hypercoagulopathy despite therapeutic heparinization - Peter Rhee; Rifat Latifi; Abbas Smiley; Kartik Prabhakaran; Joshua Klein; James K Choi; Gary Lombardo (Trauma Surgery & Acute Care Open)
Background Clinical hypercoagulopathy in patients with COVID-19 has been anecdotally described, but there is lack of evidence due to the novelty of this disease. Our study reports the results of rotational thromboelastography (ROTEM) in relation to traditional laboratory coagulation tests and acute phase markers among a cohort of severely ill, mechanically ventilated patients with COVID-19.Methods Patients with COVID-19 (N=21) with respiratory failure requiring mechanical ventilation were included in this prospective case series. ROTEM was serially obtained for all patients on three different days during their intensive care unit (ICU) stay and analyzed using repeated measures analysis. Demographic variables, symptoms at the time of presentation, ROTEM values, laboratory values for traditionally measured coagulation profiles, and acute phase reactants were analyzed, in addition to the use of anticoagulation and clinical hypercoagulopathic complications.Results The average age of our cohort was 57.9 years old (SD=14.4) and 76.2% were male. The mortality rate was 14.3% (3 of 21). Two patients (12.5%) were identified to have new-onset deep vein thrombosis, two patients (12.5%) were found to have ≥3 episodes of central venous catheter thrombosis, and three patients (18.7%) had confirmed stroke. ROTEM demonstrated elevated EXTEM and INTEM clotting times, including elevated FIBTEM maximum clot firmness (MCFFIB). All patients treated with therapeutic anticoagulation still demonstrated hypercoagulopathy within the MCFFIB tests.Discussion Repeated measure ROTEMs were able to detect hypercoagulopathy in ICU patients with COVID-19 despite therapeutic anticoagulation with heparin.Level of evidence III.